Delivery efficiency of an Elekta linac under gated operation. (8th September 2014) - Cui, Guoqiang; Housley, David J.; Chen, Fan; Mehta, Vivek K.; Shepard, David M.
Abstract : In this study, we have characterized the efficiency of an Elekta linac in the delivery of gated radiotherapy. We have explored techniques to reduce the beam‐on delay and to improve the delivery efficiency, and have investigated the impact of frequent beam interruptions on the dosimetric accuracy of gated deliveries. A newly available gating interface was installed on an Elekta Synergy. Gating signals were generated using a surface mapping system in conjunction with a respiratory motion phantom. A series of gated deliveries were performed using volumetric modulated arc therapy (VMAT) treatment plans previously generated for lung cancer patients treated with stereotactic body radiotherapy. Baseline values were determined for the delivery times. The machine was then tuned in an effort to minimize beam‐on delays and improve delivery efficiency. After that process was completed, the dosimetric accuracy of the gated deliveries was evaluated by comparing the measured and the planned coronal dose distributions using gamma index analyses. Comparison of the gated and the non‐gated deliveries were also performed. The results demonstrated that, with the optimal machine settings, the average beam‐on delay was reduced to less than 0.22 s. High dosimetric accuracy was demonstrated with gamma index passing rates no lower than 99.0% for all tests (3%/3 mm criteria). Consequently, Elekta linacs can provide a practical solution for gated VMAT treatments with high dosimetric accuracy and only a moderate increase in the overall delivery time. PACS numbers: 87.56.bd, 87.55.de, 87.55.ne